PERMASALAHAN PENATAAN RUANG KAWASAN HUTAN DALAM RANGKA REVISI RENCANA TATA RUANG WILAYAH PROVINSI - Epi Syahadat; Subarudi Subarudi (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2012)
Formulation of land use system in province area (RTRWP) and in district/city area (RTRWK)is closely related to land-use and presence of forest areas. The RTRWP formulation still have problems related to long and unsolved process of revisi on from several provinci al governments. There fore, the review on RTRWP problems is important and relevant to find its solution. The objectives of the study were to review existing policy on land-use system, to identify its problems, and to formulate strategies to solve the problems. Actually, there are regulations and policies on land-use system and forest land-uses changes, however, it needs further review on harmonization and synchronization from its substantial aspects. Problems on revision of RTRWP are: (i) revision was pushed by political force (extension of new provinces/districts), (ii) revision to save the existing non-forestry businesses, (iii) APL revision is not completed by technical and spatial review related its utilization target and realization, (iv) overlapping licenses for forestry and non-forestry businesses, (v) crop estate and other businesses at forest areas without legal license procedure from Ministry of Forestry, (vi) revision has big risks on living environment, and (vii) solution of revisionis time consuming. Strategies to solve land-use problem in RTRWP revision were: (i) changig of forest uses and function, (ii) speeding up of integrated team on changing of forest uses and function, (iii) implementing of audit for utilization of forest areas, and applying principles and guidances in forest area audit.